2018
DOI: 10.1007/s40279-018-1031-0
|View full text |Cite
|
Sign up to set email alerts
|

Football Compared with Usual Care in Men with Prostate Cancer (FC Prostate Community Trial): A Pragmatic Multicentre Randomized Controlled Trial

Abstract: BackgroundPhysical activity has been shown to mitigate the unwanted psychological and physiological side effects of prostate cancer treatments, but sustainable exercise possibilities are limited.ObjectiveOur objective was to examine whether football in a real-world setting (i.e., local football clubs) was safe and feasible in practice and could improve quality of life, mitigate decline in muscle mass and bone density, and increase fat mass in patients with prostate cancer.MethodsIn this pragmatic, multicentre,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(104 citation statements)
references
References 37 publications
3
101
0
Order By: Relevance
“…Recently, it was concluded that community-based socceris a feasible exercise strategy for men with prostate cancer and that soccer did not improve prostate cancer-specific quality of life but did improve mental health [70]. Additionally, Uth et al [49] showed that in men undergoing androgen deprivation therapy for prostate cancer, mean HR during soccer training based on four training sessions in weeks Moreover, reducing game intensity can be achieved through reducing game space while keeping the same number of players and controlling the heart rate.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, it was concluded that community-based socceris a feasible exercise strategy for men with prostate cancer and that soccer did not improve prostate cancer-specific quality of life but did improve mental health [70]. Additionally, Uth et al [49] showed that in men undergoing androgen deprivation therapy for prostate cancer, mean HR during soccer training based on four training sessions in weeks Moreover, reducing game intensity can be achieved through reducing game space while keeping the same number of players and controlling the heart rate.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…All participants gave written informed consent before initiating any trial activities. The trial was registered at ClinicalTrials.gov (NCT02430792), and we have previously reported the outcomes at 12 weeks and 6 months in full compliance with the registration [17].…”
Section: Methodsmentioning
confidence: 99%
“…Outcomes were assessed at 12 weeks, 6 months, and 1 year. The 12-week and 6-month outcome results have been reported elsewhere [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicentre randomised controlled trial (i.e., The FC Prostate Community trial) evaluating the effectiveness of community-based football programs for men with prostate cancer has shown much promise [17]. Speci cally, the football intervention (delivered in local football clubs for one hour twice weekly) was superior to the usual care (including promotion of/referral to standard rehabilitation) in mental health outcomes after six months [18], an effect sustained after 12 months in men who continued to play football [19]. Moreover, compared to men who lived alone, the study showed that men who were living with a partner adhered more regularly to the program [19].…”
Section: Introductionmentioning
confidence: 99%